Dendritic Cells and Macrophages in the Pathogenesis of Psoriasis - Kamata, Masahiro; Tada, Yayoi (Frontiers in Immunology, 2022)
Psoriasis is a chronic inflammatory skin disease characterized by scaly indurated erythema. This disease impairs patients’ quality of life enormously. Pathological findings demonstrate proliferation and abnormal differentiation of keratinocytes and massive infiltration of inflammatory immune cells. The pathogenesis of psoriasis is complicated. Among immune cells, dendritic cells play a pivotal role in the development of psoriasis in both the initiation and the maintenance phases. In addition, it has been indicated that macrophages contribute to the pathogenesis of psoriasis especially in the initiation phase, although studies on macrophages are limited. In this article, we review the roles of dendritic cells and macrophages in the pathogenesis of psoriasis.